Tempted by scandal - Booth, Karen (Karen B.) (Dynasties: secrets of the A-list., 2019)
Nadia Gonzalez has too much at stake to fall for her boss. But billionaire entrepreneur Matt Richmond has a way of getting past her defenses. Too bad what<U+2019>s amazing in the bedroom is bad for Richmond Industries<U+2014>especially when tabloid rumors threaten to destroy Nadia<U+2019>s career. Can she trust Matt to stand by her<U+2026>or must business come first?